Participatory research in low resource settings - Endeavours in epistemic justice at the Banyan, India - Mrinalini Ravi; Swarna Tyagi; Vandana Gopikumar; Emma Emily de Wit; Joske Bunders; Deborah Padgett; Barbara Regeer (Journal of Responsible Technology)
Involving persons with lived experience in knowledge generation through participatory research (PR) has become increasingly important to challenge power structures in knowledge production and research. In the case of persons with lived experiences of mental illness, participatory research has gained popularity since the early 70 s, but there is little empirical work from countries like India on how PR can be implemented in psychiatric settings.This study focuses on exploring the way persons with lived experiences of mental illness can be engaged as peer researchers in a service utilisation audit of The Banyan’s inpatient, outpatient and inclusive living facilities. The audit was an attempt by The Banyan to co-opt clients as peer-researchers, thereby enhancing participatory approaches to care planning and provision. Notes and transcripts of research process activities (three meetings for training purposes), 180 interviews as part of the audit, as well as follow up Focus Group Discussions (n = 4) conducted with 18 peer researchers, were used to document their experiences and gather feedback on the training and research process.We foundthat, reflected against the lack of formal education in the past, the opportunity and support received to be part of a research endeavour, elicited a sense of pride, relief, and liberation in peer researchers. Additionally, actualising the role of an academic and researcher, and not just being passive responders to people in positions of intellectual and systemic power, engendered a sense of responsibility and accountability to peer researchers, and to the mental health system. Thirdly, supporting persons with experiences of mental illness in participatory research activities, especially in the context of low resource settings, requires specific consideration of practical conditions and adjustments needed to avoid tokenism. Finally, both peer- and staff researchers spoke about persisting hierarchies between them which deserve attention.We conclude that participatory research has a significant scope amongst clients from disadvantaged communities in low-resource settings. Respondents repeatedly expressed an urgency for persons with lived experience to contribute to mental health pedagogy, and, in so doing, disrupt archaic treatment approaches.. Experiences from this enquiry also call for a rethink on how training in research can be developed for individuals without formal education and with cognitive difficulties, with the help of auditory support systemssuch that key concepts are available and accessible, and long-term memory becomes less of a deterrent in the pursuit of knowledge and truth.